Evolution of Scientific Production on Health Literacy and Health Education—A Bibliometric Analysis - Selva-Pareja, Laia; Ramos-Pla, Anabel; Mercadé-Melé, Pere; Espart, Anna (International journal of environmental research and public health, 2022)
In the last few years, there has been an emphasis on the importance of health literacy (HL) and health education (HE) as basic tools to empower individuals and the community. The increasing interest in HL and HE has been observed through the evolution of publications and the nature of the main trends in the last few years. Knowing how HL and HE have evolved in scientific publications can help us to identify trends and set work priorities in this scope. Based on this, a bibliometric analysis (from 2000 to 2021) was conducted in two phases: first, an analysis was performed on the publications included in the Web of Science (WOS); second, a more specific analysis was conducted on the Core Collection from WOS. The data were analyzed with two software programs, the and Bibliometrix package for RStudio, and VOSviewer to analyze number of publications, citations, authors, collaborations, keywords trends, keywords evolutions and clusters of related terms. A total of 1799 articles were found in the first phase, and 727 in the second. The results from both analyses showed that the publications increased unequally until 2020, and considerably decreased in 2021; however, in spite of this, the number of citations remained constant. Likewise, five word clusters related with HL and HE were identified. D. Nutbeam stood out as the most prolific author on the subject, the USA as the country with the most publications, and the International Journal of Environmental Research and Public Health as having the most articles on the subject. This analysis may be a useful and helpful tool for future studies on the subject.